العولمة اللغوية وتأثيرها في لغة الطفل العربي = Language globalization and its impact on the language of Arab Child - Ali, Asem Shehadeh Saleh (Kulliyyah Bahasa Arab, Sultan Abdul Halim Mu'azm Shah International Islamic University, 2018)
للعولمة اللغوية أثر فعال في ثقافة المجتمع اللغوية، من حيث إن هذه العولمة تعني هيمنة اللغة الإنجليزية بمقوماتها الثقافية على غيرها من لغات العالم، وأصبح تأثيرها يمتد إلى مدىً لم يعد الانتماء الثقافي واللغوي فيه مرتبطا بالوطن أو الدولة. وأما عمليات التحول في اللغة فتتضمن مضمونا اجتماعيا ثقافيا ينحصر في اللغة والفكر واللغة والكلام وثقافة اللغة والتعلم الثقافي للغة، ومن هنا فإن الأطفال يكتسبون اللغة عبر المعرفة الاجتماعية والسمعية والصوتية، وهم بحاجة ملحة إلى تكوينات لسانية عينية ومجردة؛ولذلك يكتسب الطفل اللغة عبر التعلم الثقافي بتكوين لساني عياني، ويكتسب اللغة عبر المحاكاة والتقليد. وهذا ما ذكرناه سوف نتناوله في دراستنا للتحولات التي تتم في لغة الطفل والناشئة العرب في ضوء العولمة اللغوية وتبعاتها الحضارية في اللغة العربية. ********************************************************* Language of globalization has effect in the linguistic culture of the community, in terms of globalization means that this predominance of English cultural valuable possession on other languages of the world, and became its influence extends to the extent no longer the cultural and linguistic affiliation is linked to the home country or state. The transformation processes in the language include guaranteed socially culturally limited in language, thought, speech, language, culture of the language, learning the cultural language, and here the children acquire language through knowledge of social, audio, voice, and they urgently need to configurations of tongue-kind and abstract; therefore, the child acquires language through learning the cultural composition of visual contact with mother tongue, and acquired the language through simulation and tradition. This is what we will search in our study of the transformations that occur in the language of children and young Arabs in the light of globalization, linguistic and cultural consequences in the Arabic language.